QIRIMTATARCA’DAKİ ALMANCA KÖKENLİ KELİME HAZİNESİ İLE ALMANCA’DAKİ TÜRKÇE KÖKENLİ KELİME HAZİNESİ ÜZERİNE BİR ARAŞTIRMA - MIESTE HOTOPP-RIECKE (Türk Uygarlığı Araştırma ve Uygulama Merkezi Dergisi, 2023)
In the first part of the article, the German-originated loan-words in the language of Crimean Tatars are discussed. The interaction between Turkic and Germanic cultures is examined during three periods: ancient, medieval and modern. It is maintained that plenty of words in Crimean Tatar language which were supposed to be borrowed from Russian, had actually been borrowed from German. The Turkic-originated loan-words in German language are discussed in the second part of the article. Some words such as kadi, kaffee, jogurt, horde and dolmetscher are discussed and are explained with Turkic-origins and some words such as basar, kiosk and diwan are explained with Persian origins which had been borrowed from Turkish.